Efeitos da suplementação de óleo de linhaça sobre o estresse oxidativo e as lesões musculares induzidos pelo exercício físico agudo - Sales, Ludmilla Christine Silva de (2020)
Performing high intensity or exhaustive physical exercises can increase the likelihood of muscle injuries and chronic fatigue due to excess free radical production, which can cause muscle damage followed by inflammatory process and impairment in muscle function. Flaxseed (Linum usitatissimim L.) has antioxidant and anti-inflammatory effect, and the oil extracted from its seeds stands out for containing a higher concentration of omega-3 when compared to other vegetable oils. It is recognized that supplementation with omega-3 fatty acid can stimulate the body's antioxidant defenses and the reduction of pro-inflammatory markers. Therefore, our objective is to investigate the effect of flaxseed oil supplementation on oxidative stress and muscle injuries induced by physical exercise. Twenty male subjects, aged 18 - 39 years, physically active and who do not have chronic non-communicable diseases. The subjects were randomly distributed into 03 groups: Group 01- Placebo + Exercise; Group 02- Flaxseed Oil (6g/day) + Exercise; Group 03 - Flaxseed Oil (12g/day) + Exercise. Supplementation was performed for 07 days. Participants were submitted to a running session on a treadmill for 40 minutes, consisting of 05 minutes of warm (4-5Km/h), 30 minutes with the intensity determined by the heart rate reached in 70-75% of VO2 maximum and 05 minutes of warm (4-5Km/h). We measured blood pressure, maximum heart rate, anthropometric variables (weight, height, waist circumference, body mass index (BMI) and body fat percentage] and biochemical parameters, and inflammatory as well as oxidative stress (glucose levels, lipid profile, lactic dehydrogenase, creatine kinase, and lipid peroxidation). Body composition, blood pressure and energy intake were similar between groups. Supplementation with 06g/day during 07 days of flaxseed oil reduced blood glucose when compared to the control group (p<0.05), however, this reduction was not observed in the group that received 12g/day of flaxseed oil. Total cholesterol, HDL and LDL levels were similar before and after the intervention. The markers of muscle injury and oxidative stress did not present alterations before, during and after the intervention, indicating that probably, the 40-minute exercise at the intensity of 70-75% of the maximum VO2 was not sufficient to promote exhaustion in the individuals and that supplementation with 06 and 12g/day flaxseed oil during one week does not result in modulation of serum concentrations of these markers.